Well-Being, Loneliness, and Quality of Relationships Before and During the COVID-19 Pandemic in Botswana - Magen Mhaka-Mutepfa; Md Jabuyer Biswas; Leonne M. Mfolwe; Kesego D. Mathoothe; M. Tasdik Hasan (SAGE Open)
This paper explored the determinants of well-being, quality of relationships (QOR), and loneliness among people of Botswana before and during the novel COVID-19 pandemic. It also examined whether there were significant differences between participants’ well-being, loneliness, and QOR before and during the COVID-19 pandemic. Factors associated with the well-being, loneliness, and QOR of the Botswana population before and during the COVID-19 pandemic were also explored. A cross-sectional design was used to collect information on the three variables before and during the COVID-19 pandemic using online platforms. Convenience sampling was used to recruit participants ( N  = 422) using the WHO-5, Three-Item Loneliness Scale, and the Relationship Quality Index (RQI). Data were analyzed using bivariate and multivariate mixed-effects linear models. Age, relationship status, concern about own and family health, difficulty switching on and off media reporting on COVID, change in lifestyle, participation in sports, and resting were significantly associated with well-being ( p  < .001) and loneliness ( p  < .05). Sleep was associated with QOR. There were significant differences in the well-being, QOR, and loneliness scores before COVID-19 conditions and during COVID-19 conditions. Stakeholders should take cognizance of the impact of predictor variables on well-being and loneliness to mitigate the impact of current and future pandemics.